The Role of Notaries in Problem Solution of Inheritance Rights - Taofik Taofik; Sri Kusriyah (Sultan Agung Notary Law Review, 2022)
The purpose of this study is to analyze and explain the role of a notary in solving inheritance rights problems. To analyze and explain the constraints and solutions to the role of a notary in solving inheritance rights problems. The method used by the researcher is Sociological Jurisdiction and specifications in this study are descriptive analytical. The sources and types of data in this study are primary data obtained from field studies with interviews. And secondary data obtained from literature studies related to the theory of justice and legal certainty. Based on the results of the study that The Role of Notaries in Settlement of Inheritance Rights Issues namely providing legal counseling, making the Deed of Separation and Distribution of Inheritance, namely: First, the Stage of Making the Deed of Declaration of Inheritance; Second, the Stage of Making SKHW; Third, the stages of making the deed of separation and distribution of inheritance. The solution is to have more control over inheritance law, whether civil, religious or customary. This is because inheritance law is one part of civil law as a whole and is the smallest part of family law which is closely related to the scope of human life. More professional in carrying out their duties. In this case, to guarantee certainty, order, and legal protection, authentic written evidence is needed regarding legal conditions, events, or actions carried out through certain positions.